Iroquois complex genes induce co-expression of rhodopsins in Drosophila. - Esteban O Mazzoni; Arzu Celik; Mathias F Wernet; Daniel Vasiliauskas; Robert J Johnston; Tiffany A Cook; Franck Pichaud; Claude Desplan (PLoS Biology)
The Drosophila eye is a mosaic that results from the stochastic distribution of two ommatidial subtypes. Pale and yellow ommatidia can be distinguished by the expression of distinct rhodopsins and other pigments in their inner photoreceptors (R7 and R8), which are implicated in color vision. The pale subtype contains ultraviolet (UV)-absorbing Rh3 in R7 and blue-absorbing Rh5 in R8. The yellow subtype contains UV-absorbing Rh4 in R7 and green-absorbing Rh6 in R8. The exclusive expression of one rhodopsin per photoreceptor is a widespread phenomenon, although exceptions exist. The mechanisms leading to the exclusive expression or to co-expression of sensory receptors are currently not known. We describe a new class of ommatidia that co-express rh3 and rh4 in R7, but maintain normal exclusion between rh5 and rh6 in R8. These ommatidia, which are localized in the dorsal eye, result from the expansion of rh3 into the yellow-R7 subtype. Genes from the Iroquois Complex (Iro-C) are necessary and sufficient to induce co-expression in yR7. Iro-C genes allow photoreceptors to break the "one receptor-one neuron" rule, leading to a novel subtype of broad-spectrum UV- and green-sensitive ommatidia.